Complete Genome Sequence of the Hyperthermophilic Piezophilic Archaeon Pyrococcus kukulkanii NCB100 Isolated from the Rebecca’s Roost Hydrothermal Vent in the Guaymas Basin - Oger, Philippe M. (Genome Announc, 2017)
Members of the order Thermococcales are common inhabitants of high-temperature hydrothermal vent systems (black smokers) that are represented in clone libraries mostly by isolates from the Thermococcus genus. We report the complete sequence of a novel species from the Pyrococcus genus, P. kukulkanii strain NCB100, which has been isolated from a flange fragment of the Rebecca’s Roost hydrothermal vent system in the Guaymas Basin.